Tick Genome Assembled: New Opportunities for Research on Tick-Host-Pathogen Interactions - de la Fuente, José; Waterhouse, Robert M.; Sonenshine, Daniel E.; Roe, R. Michael; Ribeiro, Jose M.; Sattelle, David B.; Hill, Catherine A. (Frontiers in Cellular and Infection Microbiology, 2016)
As tick-borne diseases are on the rise, an international effort resulted in the sequence and assembly of the first genome of a tick vector. This result promotes research on comparative, functional and evolutionary genomics and the study of tick-host-pathogen interactions to improve human, animal and ecosystem health on a global scale.